Convict Criminology in England: Developments and Dilemmas. (12th June 2018) - Earle, Rod
Abstract: Convict criminology is the criminology of prisoners or ex-prisoners who combine their prison experience with a higher degree in criminology. It has been associated with the carceral conditions of the United States, the exceptional scholarship of John Irwin and the activities of the US Convict Criminology group. In the United Kingdom, a vibrant prison research culture has combined with the expansion of higher education and the continued growth of prison populations to generate potential for convict criminology in England. This article combines personal experience of imprisonment, prison research and interviews with suitably 'qualified' criminologists to explore this potential. The author argues that lived experience of imprisonment can extend the boundaries of the criminological imagination and foster novel approaches to criminological practice.